Antioxidant property of NSIC Rc 238 Rice Bran extract and its cytotoxicity against human breast (MCF-7) and colon (HCT116) cancer cell lines - Usacdin, Charleen Joyce C.; Reyes, Ton Augustine F.; Maniquis, B. Kim Leileeni D.
Rice bran, a by-product of rice milling process has been reported to posses antioxidant and anticancer activities for its bioactive phytochemicals. The antioxidative property and cytotoxic activity of NSIC Rc 238 rice bran against human breast (MCF-7) and colon (HCT116) cancer cell lines. Rice bran was extracted with ethanol, which was semi-purified using modified Kupchan solvent partitioning. The ethanolic rice bran exrtacts and the different Kupchan fractions were subjected to DPPH (diphenylpicrilhydrazyl) assay for evaluation of its antioxidant property, and MTT (methylthiazoltetrazolium) assay for the evaluation of its cytotoxic activity towards MCF-7 human breast cancer and HCT116 human colon cancer cell lines. The ethyl-acetate fraction produced the highest antioxidant activity with an SC 50 value of 729.54 ug/mL, while the other extracts did not manage to reach 50% activity at 1000 ug/mL. For the cytotoxic activity, the IC50 obtained from the crude extract , dichloromethame fraction and ethyl-acetate fraction against MCF-7 were 9.25.11.94, and 7.97 ug/mL respectively, and for HCT116, 16.31, 4.86 and 7.92 ug/mL respectively. Water fraction had no significant activity on both the cancer cell lines. The extracts managed to pass the criteria set by National Cancer Institute for cytotoxicity (>20ug/mL) and were considered to be highly cytotoxic. The results of this study have shown that NSIC Rc 238 rice bran extracts have a very promising potential for anticancer drug discovery.
Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines Manila, May 2016.
Keywords: Rice bran; Antioxidants--Therapeutic use